Does media governance restrict corporate overinvestment behavior? Evidence from Chinese listed firms - Huili Zhang; Zengrui Su (China Journal of Accounting Research, 2015)
Using China's A-share listed firms from 2007 to 2011, this paper empirically tests how media governance affects firms' levels of overinvestment and whether external supervision and informal institutional mechanisms reduce these levels. We find that media governance and overinvestment are significantly negatively related. When firms are located in a district with a stronger media governance environment their levels of overinvestment are lower, indicating that media governance significantly restricts overinvestment behavior. When internal corporate governance efficiency is low, the negative relationship between the media environment and overinvestment behavior is significantly enhanced, indicating that when internal governance or formal systems have reduced efficacy, an important complementary role is played by external supervision and the informal institutional environment. After considering endogeneity and different measures of overinvestment and other related variables, the conclusions remain unchanged.
Keywords: 650; Media governance; Overinvestment; Governance efficiency